Ghana Agricultural Sector Risk Assessment : Risk Prioritization - Choudhary, Vikas; D'Alessandro, Stephen (World Bank, Washington, DC, 2015)
Improved agricultural risk management is one of the core enabling actions of the Group of Eight’s (G-8’s) New Alliance for Food Security and Nutrition. The Agricultural Risk Management Team (ARMT) of the Agriculture and Environment Services Department of the World Bank conducted an agricultural sector risk assessment to better understand the dynamics of agricultural risks and identify appropriate responses, incorporate agricultural risk perspective into decision-making, and build capacity of local stakeholders in risk assessment and management.